(3GdTQcGJ GdJLGQjIs - (3eUWai ceGd(B, (3Wgs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 1996)
(3GdCMcGe GdYGeI aj GdTQcGJ, TQcGJ GdCTNGU, TQcGJ GdCehGds
Keywords: (3GdTQcGJs; (3GdbGfhf GdJLGQjs